Pembelajaran Berbasis Proyek Untuk Meningkatkan Keterampilan Berpikir Tingkat Tinggi Peserta Didik: Analisis Pada Topik Hidrokarbon - Hidayati, Ririn Eva; Arief, Zainul (Inovasi: Jurnal Diklat Keagamaan, 2024)
The focus of this research is to describe students' high-level thinking skills using a project-based learning model in the field of chemical studies on hydrocarbon topics. This research is a quasi-experimental research that has a one-group pretest-posttest design. The objects of this research were 33 students of Class XI MAN 1 Kota Malang. The research findings show that there is an increase in students' HOTS test scores from pretest, posttest 1, and posttest 2. These results show that the project-based learning model contributes to increasing the HOTS of students at MAN 1 Kota Malang for chemistry subjects on hydrocarbon topics.